2017
DOI: 10.1186/s13578-017-0146-6
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of heme oxygenase-1 expression by curcumin conferring protection from hydrogen peroxide-induced apoptosis in H9c2 cardiomyoblasts

Abstract: BackgroundCurcumin is a major constituent of rhizomes of Curcuma longa that elicits beneficial effects for oxidative damage. The aim of this study was to investigate whether curcumin could attenuate hydrogen peroxide (H2O2)-induced apoptosis in H9c2 cardiomyoblasts and the underlying mechanisms.ResultsThe present study showed that exposure of H9c2 cells to H2O2 caused a significant increase in apoptosis as evaluated by flow cytometry analysis and the pretreatment of curcumin protected against H2O2-induced apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 33 publications
4
25
0
Order By: Relevance
“…No significant differences were found in the percentage of the TUNEL(+) hepatocytes among all groups in vivo and in vitro (Figures 5(a) and 5(b) ). Similarly, the same trend was observed in the mRNA levels of caspase3 and the bcl2/bax ratio, which are indicators of cell apoptosis related to HO-1 [ 14 ] (Figures 5(c) and 5(d) ).…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…No significant differences were found in the percentage of the TUNEL(+) hepatocytes among all groups in vivo and in vitro (Figures 5(a) and 5(b) ). Similarly, the same trend was observed in the mRNA levels of caspase3 and the bcl2/bax ratio, which are indicators of cell apoptosis related to HO-1 [ 14 ] (Figures 5(c) and 5(d) ).…”
Section: Resultssupporting
confidence: 66%
“…HO-1 exerts significant beneficial effects on the maintenance of primary liver function due to potent antiapoptotic and proproliferative properties [ 7 , 19 ]. Previous studies have provided evidence that the antiapoptotic and proproliferative effects of HO-1 involve an increased Bcl-2/Bax ratio and decreased caspase 3 [ 14 ] and p27-cell cycle inhibitor expression [ 20 ], respectively. Therefore, we speculate that the HO-1 expression level may be related to these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, curcumin reduces neuroinflammation in BV-2 microglial cells in an HO-1-dependent way (108). Besides, other studies demonstrated that curcumin could be useful to treat inflammatory diseases, by up-regulating HO-1 through PI3K/Akt signaling (109).…”
Section: Curcuminmentioning
confidence: 99%
“…In addition, the administration of curcumin can attenuate the cytotoxicity of hemiscorpius lepturus venom, which damages the mitochondrial respiratory chain and results in ATP depletion, death signaling, and consequent cardiomyocytes apoptosis [ 157 ]. Furthermore, curcumin increases the viability of H9c2 cardiomyoblasts exposed to H 2 O 2 by upregulating the HO-1 protein, inhibiting cleaved caspase-3 protein expression, and increasing the Bcl-2/Bax ratio [ 158 ]. Additionally, curcumin prevents cardiomyocytes from high glucose-induced apoptosis via the inhibition of NADPH-mediated oxidative stress by modulating the PI3K/Akt signaling pathway [ 154 ].…”
Section: Health Benefits Of Curcuminmentioning
confidence: 99%